Short-term amelioration of soil properties and maize yield enhancement using animal wastes in degraded hydromorphic soils of Southeastern Nigeria - Okenmuo F. C., Odii O. U. and Okolo C. C. (African Journal of Pig Farming, 2023)
Amending soil with animal wastes can be useful in food production as well as a means of waste disposal. It has been found to enhance physico-chemical properties and enhance yield. Poultry manure (PM), swine waste (SW), cow dung (CD), and sewage sludge (SS) were added to a hydromorphic ultisol (sandy loam, typic haplusult at the rate of 10 tha-1 (12 kgplot-1 )). Maize hybrid (Oba super II) was used as test crop. Randomized Complete Block Design (RCBD) with four replications was used in laying the experiment. Data collected were analyzed using analysis of variance (ANOVA) and means were separated using Fishers’ Least Significant Difference (F-LSD). Physical properties of soil influenced by animal wastes include bulk density, total porosity, hydraulic conductivity, gravimetric moisture contents, aggregate stability, and rheological characteristics. Amendments also enhanced soil organic matter, total nitrogen, available phosphorus, potassium, calcium, magnesium and sodium, pH, exchangeable acidity, cation exchange capacity, and base saturation were all higher relative to the unamended plots. Productivity studies revealed that maize growth was significantly affected by amendments especially PM. This was observed in height, leaf area index and yield higher relative to the control. Generally, the increase followed the order PM>SW>SS>CD. Animal wastes especially from poultry sources are recommended for soil amelioration and for increased crop yield in the area